Decree no. 310 of the year 2017 issued on 25/5/2017 on amending certain provisions of the minister of finance decree no 554 of the year 2007 concerning the rules implementing the provisions of the social insurance law promulgated by law no. 79 of the year 1975 = قرار رقم 310 لسنة 2017 الصادر بتاريخ 25/5/2017 بشأن تعديل بعض أحكام قرار وزير المالية رقم 554 لسنة 2007 بشأن القواعد المنفذة لأحكام قانون التأمين الاجتماعي الصادر بالقانون رقم 79 لسنة 1975. - Egypt; The middle east library for economic services, translator. (2025)
Ministry of social solidarity decree no. 310 of the year 2017 issued on 25/5/2017 on amending certain provisions of the minister of finance decree no 554 of the year 2007 concerning the rules implementing the provisions of the social insurance law promulgated by law no. 79 of the year 1975 -- schedule no. (8) determining earnings rates (1) building and construction works -- schedule no. (12) employer share in social insurance contributions according to the type of vehicles owned thereby وزارة التضامن الاجتماعى قرار رقم 310 لسنة 2017 بشأن تعديل بعض أحكام قرار وزير المالية رقم 554 لسنة 2007 بشأن القواعد المنفذة لأحكام قانون التأمين الاجتماعى الصادر بالقانون رقم 79 لسنة 1975 – جدول رقم (8) بتحديد نسب الأجور – جدول رقم (12) حصة صاحب العمل فى اشتراكات التامين الاجتماعى وفقاً لنواع السيارات التى يمتلكها – جدول رقم (13) أجر الاشتراك الاساسى فى تاريخ بداية الاشتراك للمؤمن عليهم من العاملين بالجهاز الإدارى للدولة والهيئات العامة الخاضعين لأحكام قانون الخدمة المدنية الذين يلتحقون الخدمة بعد 30/6/2015